Respuesta :

Answer:

3n^2=11n=6

Step-by-step explanation:

3n^2 = 3n squared

Answer:

[tex]3n^2 + 11n + 6[/tex]

Step-by-step explanation:

Key skills: Expanding Polynomials, Multiplication, Combining Like Terms

1) We are given (3n + 2)(n+3) and we need to expand this.

--> You have to use distributive property to expand this.

--> If you multiply everything out it would be --> 3n(n) + 3n(3) + 2(n) + 2(3)

--> 3n(n) = [tex]3n^2[/tex], 3n(3) = 9n, 2(n) = 2n, 2(3) = 6

--> This means it would be: [tex]3n^2 + 9n + 2n + 6[/tex]

Combine the like terms 9n and 2n to make 11n

Your final answer would be [tex]3n^2 + 11n + 6[/tex]

Hope you understood it and have a nice day!! :D